AKTIVITAS ANTIOKSIDAN EKSTRAK KULIT JENGKOL (Pithecellobium jiringa) DENGAN TIGA PELARUT YANG BERBEDA KEPOLARAN - alfin surya (JURNAL REKAYASA SISTEM INDUSTRI, 2017)
This study aims to determine the antioxidant activity based on different types of solvent in Pithecellobium jiringa extract (jengkol skin), with maceration time for 24 hours. This research used DPPH method to produce IC50 as follows: for Hexan solvent = 2688,0460 mg/mL, Ethyl acetate solvent 1279,2719 mg/mL while methanol equal to 51,1387 mg/mL